1995
DOI: 10.1007/978-1-4899-1283-1
|View full text |Cite
|
Sign up to set email alerts
|

Principles of Polymer Chemistry

Abstract: The use of general descriptive names, registered names, trademarks, service marks, etc. in this publication does not imply, even in the absence of a specific statement, that such names are exempt from the relevant protective laws and regulations and therefore free for general use. While the advice and information in this book are believed to be true and accurate at the date of publication, neither the authors nor the editors nor the publisher can accept any legal responsibility for any errors or omissions that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0
3

Year Published

2000
2000
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(42 citation statements)
references
References 0 publications
0
39
0
3
Order By: Relevance
“…Thus, it is necessary to characterize lignin in terms of average molecular weight. Two common averages used are number average molecular weight (M n ) and weight average molecular weight (M w ) (Eqns and ) . The polydispersity index (D) represents the molecular weight distribution of the polymers (Eqn ) …”
Section: Definition Of Average Molecular Weights Of Ligninmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it is necessary to characterize lignin in terms of average molecular weight. Two common averages used are number average molecular weight (M n ) and weight average molecular weight (M w ) (Eqns and ) . The polydispersity index (D) represents the molecular weight distribution of the polymers (Eqn ) …”
Section: Definition Of Average Molecular Weights Of Ligninmentioning
confidence: 99%
“…Here the index number, i , represents the number of different molecular weights present in the lignin sample and N i is the total number of moles with the molar mass of M i …”
Section: Definition Of Average Molecular Weights Of Ligninmentioning
confidence: 99%
“…They become part of the network structure and affect the viscosity and the reactivity of the formulation. Via curing with initiators the homopolymerization of the resin is effectuated . The type of curing agent defines the kind of chemical bonds, which are formed, and therefore the basic structure and the functionality of the cross‐linked matrix.…”
Section: Introductionmentioning
confidence: 99%
“…Using these two data points and solving for the water–copovidone interaction parameter, we obtained an estimated value of around 0.8. This value, being slightly larger than the critical value of 0.5 for polymer solutions, suggested that the mixing of copovidone with water was slightly unfavorable. This result could be compared to the previously reported χ value of 0.36 for the pure hydrophilic poly(vinyl pyrrolidone); this indicated slightly better mixing favorability with water .…”
Section: Resultsmentioning
confidence: 80%